Raising to the Challenge: Building a Federated Biobank to Accelerate Translational Research—The University Biobank Limburg - Linsen, Loes; Vanhees, Kimberly; Vanoppen, Evi; Ulenaers, Kim; Driessens, Suzanne; Penders, Joris; Somers, Veerle; Stinissen, Piet; Rummens, Jean-Luc (Frontiers in Medicine, 2019)
Irreproducibility of research results is one of the major contributing factors to the failure of translating basic research results into tangible bedside progress. To address this, the University Biobank Limburg (UBiLim) was founded by a collaboration between Hasselt University, the Hospital East-Limburg and the Jessa Hospital. This paper describes the evolution of this process and the barriers encountered on the way. UBiLim evolved from an archival collection over a single site biobank into a federated structure, supporting translational research at the founding institutions. Currently, UBiLim is a federated biobank, with an established organizational structure and processing and storage facilities at each of the three sites. All activities are integrated in a ISO15189 accredited Quality Management System and based on (inter)national biobank guidelines. Common methods for processing and storage of a plethora of sample types, suitable for state-of-the-art applications were validated and implemented. Because the biobank is embedded in 2 hospitals, the request of researchers to include certain sample types or enroll specific patient groups can quickly be met. Funding has been a major challenge in each step of its evolution and still remains the biggest issue for long-term biobank sustainability. To a lesser extent, the Belgian legislation and the operational cost of information management system are also concerns for smooth biobank operations. Nonetheless, UBiLim serves as a facilitator and accelerator for translational research in the Limburg area of Belgium that, given the fields of research, may have an impact on international patient care.